(untitled) (Scientific journal of the Fergana State University, 2026)
When talking about the concept of compositional speech, first of all, it is meant the consistency, content integrity, ideological and logical completion of the speech, the effective use of artistic or scientific means of expression. Speech is not only a series of language units, but a complex system consisting of their logical, grammatical and meaningful connection. The ability of a person to make a compositionally complete speech is closely related to his level of thinking, breadth of thinking and speech competence.